Pillars of Computing : A Compendium of Select, Pivotal Technology Firms - O'Regan, Gerard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This accessible compendium serves as a companion to the title Giants of Computing, examining a collection of significant technology firms that have helped to shape the field of computing and its impact on society. Each company is introduced with a brief account of its history, followed by a concise account of its key contributions. The selection covers a diverse range of historical and contemporary organizations from pioneers of e-commerce to influential social media companies. Topics and features: Presents information on early computer manufacturers, such as EMCC / Sperry / Unisys, Leo Computers, and Zuse KG Reviews important mainframe and minicomputer companies, including IBM, Amdahl, and DEC Examines the contributions to the field of semiconductors made by Intel, Texas Instruments, and Motorola Describes companies that have been active in developing home and personal computers, such as Sinclair Research, Commodore, Apple, Atari, and Dell Surveys the notable research centers Bell Labs, Xerox PARC, and the Software Engineering Institute Discusses the impact of Ericsson and Motorola in the field of telecommunications, and of SAP and Oracle in the area of enterprise software and business computing Considers the achievements of the e-commerce companies Amazon and eBay, as well as the browser wars between Microsoft and Netscape Provides a review of the social media companies Facebook and Twitter Includes coverage of such prominent companies as Adobe, Cisco, Google, HP, and Unimation Suitable for the general reader, this concise and easy-to-read reference will be of interest to anyone curious about the important role played by different technology firms in forming today s digital world. .
Background -- Adobe Systems -- Amazon.com -- Amdahl Corporation -- Apple Inc -- Atari Inc -- Bell Labs -- Cisco Systems -- Commodore Business Machines -- Dell Inc -- Digital Equipment Corporation -- Digital Research Inc -- eBay Inc -- EMCC, Sperry and Unisys -- Ericsson -- Facebook -- Google -- HP -- IBM -- Intel -- LEO Computers Ltd -- Microsoft -- Motorola -- Netscape Communications -- Oracle Corporation -- Philips -- Rational Software -- Samsung -- SAP SE -- Software Engineering Institute (SEI) -- Sinclair Research Ltd -- Texas Instruments -- Twitter -- Unimation -- Xerox PARC -- Zuse KG -- Epilogue.
Keywords: Computer science; History of Computing